The Effectiveness of the Government Internal Control System Implementation in Tegal Regency - Hadianto, Arief; Salomo, Roy V; Panggabean, Maralus (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Until the year of 2015, Tegal Regency has not gotten WTP on its financial report and there are many irregularities implementation of Regional Development Budget showed in audit report of BPK. There are some cases that resulted in a loss of regional finance, one of which is the case of the construction of Karangjambu-Guci road, which resulted in loss of regional finance equal to Rp. 1 billion more. (BPK, 2014). They are showed that the implementation of the government internal control system hasn’t been effective yet in Tegal Regency. This paper aims to describe the factors affecting implementation of The Government Internal Control System (SPIP), and to recommend solutions to overcome the difficulties of the implementation. The method of this research uses qualitative research based on a literature review and in-depth interview with some top management of Tegal Regency Administrations. The conclusions of this study are: (1) politic is a dominant factor that causes implementation of The Government Internal Control ineffective (2) commitment to the implementation of The Government Internal Control System is weak. (3) the weakness of the policy itself that there is no sanctions if violated. This paper suggest the solutions related with those issues so that the implementation of the future more effectively.